Pendampingan Penguatan Tata Kelola dan Administrasi Keuangan pada BUMDes Raharja Desa Punjul, Kecamatan Karangrejo, Tulungagung - Rika Rizki Rohmah; Zainul Asror; Purwanto Purwanto; Laela Nikmatul Wafiroh (Lembaga Pengembangan Kinerja Dosen, 2025)
BUMDes Raharja, as a village-owned economic institution, plays a strategic role in supporting local economic growth. However, preliminary assessments indicate several weaknesses in organizational governance and financial administration, particularly concerning record-keeping discipline, understanding of village financial management standards, and utilization of supporting operational documents. This community assistance research aims to strengthen institutional governance and enhance financial administrative capacity within BUMDes Raharja to ensure greater transparency, accountability, and compliance with village financial management principles. The study employs a participatory action research (PAR) approach through three main stages: (1) situation analysis and problem mapping, (2) implementation of assistance through training, technical support, and development of financial administrative instruments, and (3) evaluation through observation, document analysis, and interviews. The results show improved understanding among BUMDes administrators regarding financial administration procedures, the development of more systematic financial recording formats, and strengthened commitment to implementing more orderly and professional governance. Overall, the assistance program has had a positive impact on enhancing the managerial capacity of BUMDes Raharja as a sustainable village economic institution.